1999
DOI: 10.1103/physrevb.60.8695
|View full text |Cite
|
Sign up to set email alerts
|

Control of the electronic properties of CdSe submonolayer superlattices via vertical correlation of quantum dots

Abstract: Structural and optical properties of submonolayer CdSe/ZnSe superlattices grown with varying thickness of the ZnSe spacer layer are studied. High-resolution electron microscopy images demonstrate that submonolayer CdSe depositions result in two-dimensional nanoscale CdSe islands which are anticorrelated for spacer layer thicknesses exceeding 3 nm, while predominantly vertically correlated growth occurs for thinner spacers, in agreement with most recent theoretical predictions. Vertical ordering of the CdSe isl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 44 publications
5
45
0
Order By: Relevance
“…This particular result is in good agreement with a HRTEM study by other authors [19] for a very similar (Cd,Zn)Se/ZnSe multilayer structure (with ZnSe cladding layers of a nominal thickness of 3 nm and CdSe sheets of nominally the same thickness as in our study).…”
Section: A Ii-vi Quantum Dotssupporting
confidence: 93%
“…This particular result is in good agreement with a HRTEM study by other authors [19] for a very similar (Cd,Zn)Se/ZnSe multilayer structure (with ZnSe cladding layers of a nominal thickness of 3 nm and CdSe sheets of nominally the same thickness as in our study).…”
Section: A Ii-vi Quantum Dotssupporting
confidence: 93%
“…[11][12][13][14][15] However, despite the fact that elastic interactions favor lateral ordering of islands as well, they turned out to be rather weak 16 and only rather short-range ordering was observed in the above mentioned systems by atomic force microscopy, transmission electron microscopy, and x-ray diffraction ͑XRD͒. [16][17][18][19][20][21] Apart from vertical island ordering in columnar form, in III-V, 22,23 II-VI, [24][25][26] and IV-VI compounds 27 also oblique ordering was observed, 28 typically for larger spacer layer thicknesses, before for sufficiently wide spacers the ordering finally vanishes. 29 For the PbSe/PbEuTe system the formation of a three-dimensionally ͑3D͒ ordered trigonal island crystal in PbSe island multilayers separated by PbEuTe spacer layers was observed for a certain range of the spacer layer thickness for growth along an elastically soft ͓111͔ direction.…”
Section: Introductionmentioning
confidence: 99%
“…Early reports cover the dependence of correlation and anticorrelation in short period submonolayer stacks [7] on stacking conditions like barrier thickness. Litvinov et al [8] demonstrated coherently stacked islands obtained at elevated growth temperatures of 400 C in triple stacks if the barrier thickness corresponded to 12-20 monolayers (ML), while for a smaller thickness a complete intermixing due to inter-diffusion occurred.…”
mentioning
confidence: 99%